Developmental delay and failure to thrive associated with a loss‐of‐function variant in WHSC1 (NSD2). Issue 12 (22nd October 2018) - Boczek, Nicole J.; Lahner, Carrie A.; Nguyen, Thuy‐mi; Ferber, Matthew J.; Hasadsri, Linda; Thorland, Erik C.; Niu, Zhiyv; Gavrilova, Ralitza H.
Abstract : Wolf‐Hirschhorn syndrome (WHS) is a microdeletion syndrome characterized by distinctive facial features consisting of "Greek warrior helmet" appearance, prenatal and postnatal growth deficiency, developmental disability, and seizures. This disorder is caused by heterozygous deletions on chromosome 4p16.3 often identified by cytogenetic techniques. Many groups have attempted to identify the critical region within this deletion to establish which genes are responsible for WHS. Herein, clinical whole exome sequencing (WES) was performed on a child with developmental delays, mild facial dysmorphisms, short stature, failure to thrive, and microcephaly, and revealed a de novo frameshift variant, c.1676_1679del (p.Arg559Tfs*38), in WHSC1 ( NSD2 ). While WHSC1 falls within the WHS critical region, individuals with only disruption of this gene have only recently been described in the literature. Loss‐of‐function de novo variations in WHSC1 were identified in large developmental delay, autism, diagnostic, and congenital cardiac cohorts, as well as recent case reports, suggesting that de novo loss‐of‐function WHSC1 variants may be related to disease. These findings, along with our patient suggest that loss‐of‐function variation in WHSC1 may lead to a mild form of Wolf‐Hirschhorn syndrome, and also may suggest that the developmental delays, facial dysmorphisms, and short stature seen in WHS may be due to disruption of WHSC1 gene.